A constituição de identidades em pronunciamentos de posse presidencial: o eu enunciador e o povo brasileiro - Araújo, Annyelle de Santana (2015)
Thinking about the statements is to think about what has been actually said. The statements occupy a place which only belongs to them and exclude all the other possibilities. And they are still capable to constitute many things, including identities. In this assignment, we analyzed how the statements which form the presidential inauguration speeches constitute identities as of the enunciator (the one who occupies, in the moment of the statement, the position – President of the Republic) as of the Brazilian people. For the analyses, we selected two Brazilian historical moments: Military Dictatorship and after-dictatorship. From the first moment, we selected two inauguration statements : Castello Branco (1964), for being the first military to be appointed to president and João Batista Figueiredo (1979) for being the last general who assumed the position in the period, in other words, we selected the beginning and the ending of the militarism. From the second moment we selected three statements: Fernando Collor (1990) for having been the first president elected by the direct vote after the dictatorship, Lula (2003) who represents the first time his party elected a candidate to the function and because of the social claim which he always had and Dilma Rousseff (2011) for having been the first woman elected to the presidency and because she represented the continuation of the last government. For we do these identity analysis, we started from the notion proposed by Michel Foucault and from the notion of identity of Bauman. We worked with the hypothesis that the enunciator when saying his statement launches identities which are fundamental for the maintenance of the Biopower and this is just what we identified. Each one of the statements constitute different identities (although we have found some irregularities like the exaltation of positive and negative aspects) which are reflexes of the emergencies of the society in that social-historical moment and they work as a warranty of the good execution of the proposals of the government.